2016
DOI: 10.1016/j.biortech.2016.08.080
|View full text |Cite
|
Sign up to set email alerts
|

Flocculation properties of several microalgae and a cyanobacterium species during ferric chloride, chitosan and alkaline flocculation

Abstract: Flocculation properties of several microalgae and a cyanobacterium species during ferric chloride, chitosan and alkaline flocculation, Bioresource Technology (2016), doi: http://dx.doi.org/10.1016/j.biortech.2016.08.080 Archived versionAuthor manuscript: the content is identical to the content of the published paper, but without the final typesetting by the publisher This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(63 citation statements)
references
References 32 publications
0
59
0
1
Order By: Relevance
“…Flocculation is an economical method for biomass recovery; however, usually, one method does not have a similar yield for different microalgae and cyanobacteria. Therefore, flocculant dosage is an important factor in the selection of the candidate cyanobacterial isolate to produce biofuel . Beside direct application of cyanobacteria for the biofuel production, they can be used as a feed supply for eukaryotic microalgae which can produce biodiesel feedstock.…”
Section: Economical Point Of Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…Flocculation is an economical method for biomass recovery; however, usually, one method does not have a similar yield for different microalgae and cyanobacteria. Therefore, flocculant dosage is an important factor in the selection of the candidate cyanobacterial isolate to produce biofuel . Beside direct application of cyanobacteria for the biofuel production, they can be used as a feed supply for eukaryotic microalgae which can produce biodiesel feedstock.…”
Section: Economical Point Of Viewmentioning
confidence: 99%
“…Therefore, flocculant dosage is an important factor in the selection of the candidate cyanobacterial isolate to produce biofuel. 133 Beside direct application of cyanobacteria for the biofuel production, they can be used as a feed supply for eukaryotic microalgae which can produce biodiesel feedstock. Nascimento et al 134 indicated that the biomass of Nfertilizer cyanobacterium, Nostoc sp.…”
Section: Bioinformatic Studiesmentioning
confidence: 99%
“…Lama et al even showed that chitosan is not able to induce the formation of Nannochloropsis sp. flocs . As the chitosan was dissolved in acetic acid, the pH of the culture decreased to 6–7.…”
Section: Resultsmentioning
confidence: 99%
“…The hydroxymethylation reaction occurred easily under neutral or alkaline condition, thereby resulting in a decrease in the intrinsic viscosity and the grafting efficiency of the polymer [38]. Meanwhile, the effect of hydrogen bonding was strengthened by the protonation of most carboxylic acids and quaternary ammonium groups in an acidic environment, thereby playing a negative role in improving the intrinsic viscosity of CPCTS-g-P (CTA-DMDAAC) [39]. Therefore, the optimal pH range is 4-6.…”
Section: Effect Of Photo-initiator Concentration On Intrinsic Viscosimentioning
confidence: 99%